Simultaneous rhytidectomy and orthognathic surgery. Is it possible?. (February 2023) - Verona, P.; Solano, N.; Rivera, E.; Peraza, A.; Fuenmayor, L.
Abstract : Purpose: To demonstrate that it is possible to perform a rhytidectomy simultaneously with orthognatic surgery through a clinical case. Methods: A 52-year-old woman presented with significant class II dentofacial deformity, mandibular hypoplasia and facial lipodystrophy. Her surgical procedure involved bilateral sagittal ramus osteotomy and genioplasty advancement with rhytidectomy simultaneously. Results: 6 months postoperatively, occlusal stability was observed, facial wounds in a healthy healing process, without evidence of keloids or hypertrophies, the patient does not have sensory or motor nerve damage and reports great satisfaction with the result. Conclusions: It should be noted that the patient decides to undergo surgery for aesthetic reasons while the surgeon proposes a surgery that improves his function. Rhytidectomy is one of the surgical procedures that can be performed simultaneously with othognatic surgery. We must always keep in mind the changes in the facial soft tissues that occur with skeletal movements and the intraoperative edema typical of the surgical act, taking into account the increase in operative time that carries out both surgeries simultaneously.